Biomass, Biorefineries and Bioeconomy - Samer, Mohamed (IntechOpen, 2022)
This book comprehensively reviews biomass and bioeconomy, biomass production and treatment, biomass utilization, biomass biorefineries, and bioenergy generation from biomass. It discusses topics focusing on the concept of circular and sustainable bioeconomy, economic assessment of biomass utilization, biomass valorization, biomass pretreatment, bioprocessing of biomass using integrated bioindustrial systems, and production of value-added biochemicals and bioenergy from biomass.